2010
DOI: 10.1136/ard.2010.134965
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of enthesis ultrasound in the diagnosis of early spondyloarthritis

Abstract: Entheses are affected early in spondyloarthritis, and the incidence of involvement is higher in men and independent of the spondyloarthritis diagnostic subtype, HLA-B27 status or presentation pattern. The enthesis ultrasound score seems to have diagnostic accuracy and may be useful for improving the diagnostic accuracy of early spondyloarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 25 publications
1
47
0
6
Order By: Relevance
“…In this cohort the prevalence of peripheral enthesitis was independent of the clinical phenotype (axial or peripheral), consistent with observations in established SpA 22. In agreement with our previous observation and recent Spanish studies, we confirmed that the number of entheses involved and the PDUS global score could distinguish SpA from non-SpA with good sensitivity and specificity 22 24 27. Strikingly, we also confirmed that vascularisation of the enthesis insertion by PDUS is a landmark feature for SpA, even in suspected cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this cohort the prevalence of peripheral enthesitis was independent of the clinical phenotype (axial or peripheral), consistent with observations in established SpA 22. In agreement with our previous observation and recent Spanish studies, we confirmed that the number of entheses involved and the PDUS global score could distinguish SpA from non-SpA with good sensitivity and specificity 22 24 27. Strikingly, we also confirmed that vascularisation of the enthesis insertion by PDUS is a landmark feature for SpA, even in suspected cases.…”
Section: Discussionsupporting
confidence: 92%
“…However, some of them have insufficient sensitivity in some situations (x-rays, MRI) or incomplete specificity (HLA-B27 typing) 26. Thus, the high sensitivity and specificity of detecting enthesitis by PDUS in established and early SpA led us to consider it as a candidate diagnostic tool 22 24 27…”
Section: Discussionmentioning
confidence: 99%
“…However, no cutoff level for the GUESS score has been established to differentiate between patients and normal controls. The Madrid Sonographic Enthesitis Index has a recommended cutoff level for spondyloarthropathy [29,30], but we did not use it because it has a relatively complicated scoring method (score range, 0e136).…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of novel effective therapies for SpA that can reduce disease activity and improve quality of life, early correct diagnosis, and classification of patients presenting with symptoms suggestive of SpA becomes crucial. De Miguel et al 27 assessed the accuracy of enthesis ultrasound assessment for early diagnostic classification of SpA. Patients with mixed probability of having SpA were scanned and scored for enthesis abnormalities using the MASEI method.…”
Section: The Clinical Uses Of Ultrasound Scanning Of the Enthesis In Spamentioning
confidence: 99%